Too much trick or treat - Miller, Jayna, 1969- (Kansas City, Mo. : Landmark Editions, 1991)
Jammer the Rabbit's classmates get even when Jammer absconds with all the Halloween treats.
13 19 21 29
Keywords: Halloween -- Fiction; Behavior -- Fiction; Rabbits -- Fiction; Animals -- Fiction